Правові проблеми впливу нелегальної міграції на національну безпеку України - Гороть, А.; Прокопчук, К.; Horot, A.; Prokopchuk, K. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті зроблено спробу висвітлити проблему нелегальної міграції як соціально небезпечного явища, що стала актуальною для України практично одночасно після її утворення як самостійної держави та становить на цей час реальну загрозу національній безпеці України. Міграція населення є одним із численних аспектів глибокої й усеохоплюючої системної кризи в Україні. Проблема трудової міграції належить до тих явищ, які безпосередньо впливають на всі без винятку суспільні процеси.In the article we are trying to highlight the problem of illegal migration, as a socially dangerous phenomenon, which became actual for Ukraine after it had become an independent state and it is a real threat to the national security of Ukraine. Migration of the population is one of the many aspects of a deep and comprehensive system crisis in Ukraine, and this is no secret to the public. It doesn’t require any proof that this systemic crisis, not some external factors, is exactly the greatest threat to the national security of our country. But if the vast majority of the crisis components can be seen by the limited social circles, well-informed because of professional and official duties (administration at various levels, deputies, journalists, intelligence services and security agencies, experts), the problem of labor migration refers specifically to those that transpierce the society, are present in everyday life of almost every Ukrainian family and directly influence on every single social processes.
Legal Problems of the Influence of the Illegal Migration on the National Security of Ukraine.
Keywords: багатосторонні відносини; двосторонні відносини; національна безпека; multilateral relations; bilateral relations; national security